A catalytic DNA circuit-programmed and enzyme-powered autonomous DNA machine for nucleic acid detection. Issue 20 (17th September 2019) - Liu, Shuang; Xin, Chen; Yu, Xiaoxiao; Ding, Zhenbo; Liu, Shufeng
Abstract : A catalytic DNA circuit-programmed and enzyme-powered autonomous DNA machine was proposed for one-step, isothermal and dual-level amplified detection of nucleic acids. Abstract : A catalytic DNA circuit was ingeniously engineered to harness the cleavage of a nicking endonuclease on a triple-stranded duplex DNA probe, autonomously actuating a successive enzyme-powered DNA machine for one-step, isothermal, and autocatalytic nucleic acid analysis. The detection performance could be tuned with or without the use of enzymes.